Data retention in organic ferroelectric resistive switches - Khikhlovskyi, Vsevolod; Breemen, Albert J. J. M. van; Janssen, René A. J.; Gelinck, Gerwin; Kemerink, Martijn (Organic electronics, 2016)
Solution-processed organic ferroelectric resistive switches could become the long-missing non-volatile memory elements in organic electronic devices. To this end, data retention in these devices should be characterized, understood and controlled. First, it is shown that the measurement protocol can strongly affect the ‘apparent’ retention time and a suitable protocol is identified. Second, it is shown by experimental and theoretical methods that partial depolarization of the ferroelectric is the major mechanism responsible for imperfect data retention. This depolarization occurs in close vicinity to the semiconductor-ferroelectric interface, is driven by energy minimization and is inherently present in this type of phase-separated polymer blends. Third, a direct relation between data retention and the charge injection barrier height of the resistive switch is demonstrated experimentally and numerically. Tuning the injection barrier height allows to improve retention by many orders of magnitude in time, albeit at the cost of a reduced on/off ratio.